Glycopeptide antibiotic drug stability in aqueous solution - Sardar M. Jakaria; David E. Budil; James Murtagh (AAPS Open, 2022)
Abstract Glycopeptide antimicrobials are a class of naturally occurring or semi-synthetic glycosylated products that have shown antibacterial activity against gram-positive organisms by inhibiting cell-wall synthesis. In most cases, these drugs are prepared in dry powder (lyophilized) form due to chemical and physical instability in aqueous solution; however, from an economic and practical point of view, liquid formulations are preferred. Researchers have recently found ways to formulate some glycopeptide antibiotic therapeutic drugs in aqueous solution at refrigerated or room temperature. Chemical degradation can be significantly slowed by formulating them at a defined pH with specific buffers, avoiding oxygen reactive species, and minimizing solvent exposure. Sugars, amino acids, polyols, and surfactants can reduce physical degradation by restricting glycopeptide mobility and reducing solvent interaction. This review focuses on recent studies on glycopeptide antibiotic drug stability in aqueous solution. It is organized into three sections: (i) glycopeptide antibiotic instability due to chemical and physical degradation, (ii) strategies to improve glycopeptide antibiotic stability in aqueous solution, and (iii) a survey of glycopeptide antibiotic drugs currently available in the market and their stability based on published literature and patents. Antimicrobial resistance deaths are expected to increase by 2050, making heat-stable glycopeptides in aqueous solution an important treatment option for multidrug-resistant and extensively drug-resistant pathogens. In conclusion, it should be possible to formulate heat stable glycopeptide drugs in aqueous solution by understanding the degradation mechanisms of this class of therapeutic drugs in greater detail, making them easily accessible to developing countries with a lack of cold chains.